2-fluoro-5-maleimidobenzoic acid-linked albumin drug (MAD) delivery for selective systemic targeting of metastatic prostate cancer - Akinboye, Emmanuel S. (Prostate, 2018)
BACKGROUND: The SH-group at Cys-34 of human serum albumin (HSA) is a unique and accessible functional group that can be exploited for efficient linkage of a maleimide containing cytotoxic drug derivative to albumin. The specific maleimide chemistry used for production of the maleimide-linked albumin drug (MAD) is critical, however, to minimize the plasma concentration of “free” cytotoxic drug spontaneously released from albumin carrier thus decreasing dose-limiting host toxicity while enhancing the plasma half-life from minutes to days (ie, pharmacokinetic effect) and tissue concentration of the MAD in the extracellular cellular fluid at sites of cancer (ie, EPR effect). METHODS: To accomplish this goal, a chemical synthesis was developed using 2-fluoro-5-maleimidobenzoic acid to stably link the potent cytotoxic chemically modified analogue of the naturally occurring sesquiterpene γ-lactone, thapsigargin, 8-O-(12-aminododecanoyl)-8-O-debutanoyl thapsigargin (12ADT), to Cys-34 of albumin to produce 12ADT-MAD. RESULTS: Using FITC-labeling, LC/MS analysis, and in vitro growth and clonogenic survival assays on a series of 6 human prostate cancer lines (LNCaP, LAPC-4, VCap, CWR22R(v)1, PC3, and Du145), we documented that 12ADT-MAD is endocytosed by prostate cancer cells where it is degraded into its amino acids liberating cysteinyl-maleimide-12ADT which is both chemically stable at the acidic pH of 5.5 present in the endosome while retaining its high killing ability (IC(50) 50 nM) via SERCA inhibition. CONCLUSIONS: Based upon these positive in vitro validation results, the in vivo efficacy versus host toxicity of this 12-ADT-MAD approach is presently being evaluated against a series of patient derived androgen responsive and castration resistant human xenografts in immune-deficient mice.